1996
DOI: 10.1021/jf950501h
|View full text |Cite
|
Sign up to set email alerts
|

Atrazine Sorption by a Mineral Soil:  Effects of Soil Size Fractions and Temperature

Abstract: Equilibrium, kinetics, and mechanism of sorption of the herbicide atrazine by a mineral soil (GB 843) have been studied with an on-line microfiltration-HPLC technique combined with a batch design. As a continuation of our previous work, this paper presents the results of a study of soil size fractionation and the effect of temperature. The experiments with soil size fractions revealed only relatively small changes in atrazine uptake. As expected, the experiments with varying temperature from 5 to 35°C have sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
(18 reference statements)
1
16
1
1
Order By: Relevance
“…This indicates that at warmer temperatures more 14 C residue was able to become bound or nonextractable with time, leaving less available to diffuse into the water column (Mersie et al, 1998a). These results are consistent with Li et al (1996) in which irreversible uptake was characterized by an effective diffusion coefficient (D) that increased by a factor of 40 from 5 to 35 °C. The compounds are becoming sequestered in inaccessible microsites within the sediment matrix (Alexander, 1995).…”
Section: Resultssupporting
confidence: 80%
“…This indicates that at warmer temperatures more 14 C residue was able to become bound or nonextractable with time, leaving less available to diffuse into the water column (Mersie et al, 1998a). These results are consistent with Li et al (1996) in which irreversible uptake was characterized by an effective diffusion coefficient (D) that increased by a factor of 40 from 5 to 35 °C. The compounds are becoming sequestered in inaccessible microsites within the sediment matrix (Alexander, 1995).…”
Section: Resultssupporting
confidence: 80%
“…Either they do not degrade at all or their half-lives are very large under measured aquifer conditions. Degradation of atrazine in soils is studied by numerous authors (Agertved et al, 1992;Li et al, 1996;Beck & Jones, 1996) and is microbiologically triggered. However, at greater depths persistence increases as described by Fomsgaard (1995) for the subsoil and by Klint et al (1993) for certain aquifer environments, which can possibly attributed to lower microbial activities with increasing depths.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that herbicide concentrations were greatest on wind-erodible sediments regardless of incorporation treatment. Both Novak et al (1994) and Li et al (1996) also reported unequal herbicide distribution across size fractions after application. This can be explained partially by examining the surface area to volume ratio of different size fractions (Figure 1).…”
Section: Incorporation Effectsmentioning
confidence: 99%